A self-sustaining nanoplatform overcomes TRAIL-resistance of pancreatic cancer by a source-broadening and expenditure-reducing apoptosis strategy - Xianzhou Huang; Haijun Li; Chunqing Ou; Yaqian Shu; Rui Luo; Xinchao Li; Shouchun Chen; Qinjie Wu; Changyang Gong; Lei Liu (Materials & Design, 2021)
Pancreatic cancer generates resistance to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) by downregulating death receptors and switching pro-apoptosis to anti-apoptosis through caspases blockers like X-linked inhibitor of apoptosis proteins (XIAPs) and survivin. From this perspective, a self-sustaining nanoplatform (SSN) was prepared to reverse the downregulation of death receptors and remove blockage of XIAPs and survivin as a source-broadening and expenditure-reducing strategy to coactivate extrinsic and intrinsic apoptosis in TRAIL-resistant pancreatic cancer. After administration, efficient tumor accumulation and cellular uptake of SSN would be achieved by elongated circulation time of PEG shell and active targeting ability of novel multifunctional R6ST protein equipped with cell-penetrating peptide R6 and active targeting of soluble TRAIL fragment, and further enhanced through interaction with the death receptors upregulated by the encapsulated celecoxib in SSN, which could be served as a positive feedback loop. This positive feedback loop not only broadened the source of death receptors but also reduced the expenditure of caspases by counteracting the inhibition of XIAPs and survivin via tetrapeptides AVPI in R6ST and celecoxib respectively, to synchronously relieve and promote exogenous and endogenous apoptotic pathway. Consequently, SSN exhibited synergistic effect to overcome TRAIL-resistance of pancreatic cancer through this source-broadening and expenditure-reducing strategy.